Prediction of stable structure and unique charge transfer in Li–Pt intermetallic compounds under pressure - Wenlin Xu; Dengjie Yan; Liguo Zhu; Yifei Wang; Lingxin Kong; Bin Yang; Baoqiang Xu (Journal of Materials Research and Technology)
The exploration of new intermetallic compounds is of great significance for basic research and practical application. There is a huge electronegativity difference between Li and Pt, and the metals exhibit interesting and diverse properties; however, the structural behavior of Li–Pt intermetallics with different ratios under high pressure has not been systematically studied. In this study, an intelligent structure search method based on a particle swarm optimization algorithm combined with first-principles calculations was used to extensively explore the stable structures and unique conditions governing charge transfer in Li–Pt intermetallic compounds under different pressures. In addition to reproducing the known LiPt (P 6‾ m2) and Li2Pt (P6/mmm), the simulation was consistent with the experimental results. New phases were also found by calculation: LiPt3(Cmmm), Li2Pt (P 3‾ m1), and Li4Pt (I4/m) at ambient pressure; Li3Pt (Fm 3‾ m), Li4Pt (R 3‾ m), and Li5Pt (P6/mmm) at 10 GPa; and Li5Pt (P 3‾ m1) at 20 GPa. Bader charge analysis and electron localization function (ELF) mapping showed that the transition metal (Pt) atoms exhibit unusual oxidation states both under ambient and high pressure, and more electrons were localized on Pt as the Li content increased. The highest negative valence state was approximately −4. Intermetallic compounds LiPt3 (Cmmm) and Li2Pt (P6/mmm) were prepared successfully by arc melting furnace. The reliability of structure prediction method and pseudo potential selection was verified. This work demonstrates that tuning the pressure and stoichiometry is an effective means of forming novel, stable intermetallic compounds.